2018
DOI: 10.1371/journal.pone.0195834
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer and Cryptosporidium spp. infection

Abstract: Transient or constant impaired immunity is often associated with neoplastic disease or oncological treatment. Among the most common pathogens found in patients with HIV or patients undergoing chemotherapy are protozoans of the Cryptosporidium genus, which cause diarrhea in humans and animals. The present study determined the frequency of Cryptosporidium spp. infections in patients with colorectal cancer (N = 108; 42 women; 66 men; median age, 65 years), before beginning oncological treatment, compared to a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 40 publications
4
50
1
Order By: Relevance
“…Several epidemiological studies demonstrated that colorectal cancer is highly correlated with Cryptosporidium spp. [10][11][12][13][14]. In consistence, we here found that 17.24% patients with colorectal cancer had C. parvum infections, which was significantly higher than control population.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Several epidemiological studies demonstrated that colorectal cancer is highly correlated with Cryptosporidium spp. [10][11][12][13][14]. In consistence, we here found that 17.24% patients with colorectal cancer had C. parvum infections, which was significantly higher than control population.…”
Section: Discussionsupporting
confidence: 49%
“…In 2007, the first epidemiological study in Poland showed that 10 out of 55 (18%) patients with diagnosed colorectal cancer had cryptosporidiosis, and the infection rate was even higher in those patients with diarrhea symptom (43.5%, 10/55) [10]. Another two reports also conducted in Poland showed similar infection rates (12.6%, 11/87 and 13%, 14/108) [11,12]. Recently, Osman M. et al (2017) performed a systematic analysis among Lebanese patients which indicated that Cryptosporidium spp.…”
Section: Ivyspringmentioning
confidence: 96%
“…Epidemiological studies have shown an association between colorectal cancer and Cryptosporidium spp. infection (Osman et al, 2018; Sulzyc-Bielicka et al, 2018). Furthermore, a limited number of experimental studies have shown that C. parvum induces neoplastic changes in immunocompromised animals and in cells cultured in vitro , consistent with a role in carcinogenesis (Benamrouz et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptosporidium is a common opportunistic pathogen in immunodeficient/immunocompromised individuals, especially HIV-infected patients, cancer patients and children younger than 5 years old [10,29,37]. In the present study, one case was a cancer patient and another was a child younger than 5 years old, both of whom were susceptible to Cryptosporidium.…”
Section: Discussionmentioning
confidence: 59%